DEVELOPING CREATIVE INDUSTRY -BASED ORAL TRADITION - Anoegrajekti, Novi (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study aims to develop a creative industry -based oral traditions mediated by language. Oral traditions serve as one of the media that embody local wisdom. The development of creative industries rooted in oral traditions simultaneously functions as a strategy for preserving local cultural values. The development of the creative industry is carried out through an integrated process involving the production of language-based content, the adaptation of oral literature, visual design, and digital marketing strategies. The second stage identifies oral traditions and local wisdom with the potential to serve as the foundation for creative industry development. The third stage identifies alternative creative industry products by utilizing local materials that act as markers of local identity. Furthermore, the development of creative industries is conducted by engaging younger generations to ensure the socialization and internalization of local cultural values while prioritizing cultural, environmental, and economically beneficial education through enjoyable and relevant approaches, such as short videos, online comics, T-shirt designs, and other creative products. Culture in general, and oral traditions in particular, continue to be practiced and lived within communities, which means they maintain their potential for further development as sources of economic value.